Do mobile consumers homogenize the distribution of resources in stream food webs? A test with overlapping fish and mussel aggregations. (27th December 2021) - Vaughn, Caryn C.; Parr, Thomas B.; DuBose, Traci P.; Gates, Kiza K.; Hopper, Garrett W.; Gido, Keith B.
Abstract: In streams, unionoid mussels and fish form aggregations that exert bottom‐up and top‐down effects on food webs, but the magnitude and spatial extent of their effects are controlled by species traits. Sedentary mussels live burrowed in the sediment in patchily distributed dense aggregations (mussel beds) where they filter seston and provide a local, relatively constant nutrient subsidy. In contrast, fish move on and off mussel beds, and thus comprise a transient nutrient subsidy. We asked how overlap between fish and mussels influences nutrient recycling and resource distribution in streams. We conducted an 8‐week study in experimental streams where we created mussel beds (comprised of two species, Actinonaias ligamentina and Amblema plicata ), manipulated the occurrence of a grazing minnow ( Campostoma anomalum ), and tracked nutrient (nitrogen and phosphorus) and resource (algae, detritus, and chironomids) abundance up and downstream of the mussel beds. In general, neither consumer had strong effects on the concentration or spatial distribution of nutrients. Water turnover time in our experimental streams may have diluted fish and mussel nutrient excretion effects, making it difficult to detect spatial patterns during a given sampling period. Fish controlled the abundance and productivity of algae. In treatments without fish, large mats of filamentous algae formed early in the experiment. These algae senesced, decomposed, and were not replaced. When fish were present, algae consisted of attached biofilms with consistent biomass and spatial distribution over time. Although previous work has shown that mussels can have strong, seasonal bottom‐up effects on both primary and secondary production, our results suggested that adding grazing mobile fishes, led to a more consistent and homogenous supply of algal resources. Because mussels rarely occur in the absence of fish, considering their combined influence on ecosystem dynamics is likely to be important.